2021
DOI: 10.1097/ncc.0000000000000930
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, Death Perception, and Spiritual Well-Being in Adult Oncology Patients

Abstract: Background Holistic nursing care requires taking into consideration the spiritual and emotional dimensions of the patient. Objective The aim of this study was to determine the relationships among loneliness, death perception, and spiritual well-being in adult oncology patients. Methods This cross-sectional, descriptive-correlational study was conducted between March 20, 2018, and September 20, 2018. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Urological cancer patients usually suffer from social or self-isolation, poor spiritual status, and fear of death, which might result in a reduced quality of life and increased mortality ( 14 , 19 ). The present study found that loneliness was higher and spiritual well-being was lower in urological cancer patients than in healthy controls, which was partly in line with previous studies that indicated that loneliness and reduced spiritual well-being were prevalent in cancer patients ( 12 , 14 , 20 ). Urological cancer patients have low self-esteem and might also feel a loss of self-worth, which results in less social interaction with others and ultimately contributes to increased loneliness ( 21 , 22 ); it should be mentioned that a previous study reported that loneliness was indirectly responsible for the occurrence of depression in prostate cancer patients ( 23 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Urological cancer patients usually suffer from social or self-isolation, poor spiritual status, and fear of death, which might result in a reduced quality of life and increased mortality ( 14 , 19 ). The present study found that loneliness was higher and spiritual well-being was lower in urological cancer patients than in healthy controls, which was partly in line with previous studies that indicated that loneliness and reduced spiritual well-being were prevalent in cancer patients ( 12 , 14 , 20 ). Urological cancer patients have low self-esteem and might also feel a loss of self-worth, which results in less social interaction with others and ultimately contributes to increased loneliness ( 21 , 22 ); it should be mentioned that a previous study reported that loneliness was indirectly responsible for the occurrence of depression in prostate cancer patients ( 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding death perception, the current study showed that fear of death, death avoidance, and approaching death acceptance were higher but neutral acceptance of death was lower in urological cancer patients than in healthy controls. It is known that urological cancer patients experience tremendous physical pain and psychological stress, which might make them feel that death is close ( 20 , 27 ); therefore, fear of death and death avoidance are obvious in urological cancer patients. In addition, the survival of urological cancer patients is shorter than normal people ( 2 ); hence, urological cancer patients might consider that life is unfair to them, leading to lower neutral acceptance of death.…”
Section: Discussionmentioning
confidence: 99%
“…In overcoming diseases and resisting difficulties caused by illness, spiritual well‐being plays an important role (Kavak et al., 2021). Previous research has shown that patients with higher levels of spiritual well‐being have a more positive perspective on death, helping to ease patients' fear of dying (Kavalali Erdogan & Koc, 2021). Resilience belongs to positive psychology, which refers to the ability of a person to cope effectively and adapt well in the face of difficulties brought about by illness, and is a self‐protective capacity (Herrman et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual well-being is a component of health-related quality of life (HRQOL) and increased spiritual well-being has been shown to have a positive effect on a person’s quality of life ( Munoz et al ., 2015 ; Ahmad et al ., 2022 ). Studies have highlighted a relationship between spiritual well-being and health promotion, as well as coping mechanisms for various populations, including people with cancer ( Damen et al ., 2021 ; Kavalali Erdoğan & Koç, 2021 ), older adults in nursing homes ( Santana-Berlanga et al ., 2020 ; Rykkje et al ., 2023 ) and those at risk of suicide while living with chronic healthcare issues ( Loureiro et al ., 2018 ).…”
Section: Introductionmentioning
confidence: 99%